The Analysis of Literal Meaning and Non-Literal Meaning in William Shakespeare's Poetry - Putri Dwi Gustiana; Maisarah, Ira (Journal of English for Specific Purposes in Indonesia, 2023)
One of the best poetry is William Shakespeare's poetry. Poetry has a literal meaning and a non-literal meaning. This research aims to found what is the dominant non-literal meaning in Shakespeare's poetry and what is the literal meaning of each non-literal meaning in that poetry. The researcher used the descriptive method to describe the literal meaning and non-literal meanings in these William Shakespeare's poetry. This study found that the dominant type of non-literal meaning in this Shakespeare’s poetry is metaphor.